Fischer‐Tropsch synthesis: Effect of solvent on the H2‐D2 isotopic exchange rate over an activated cobalt catalyst. (24th February 2016) - Pendyala, Venkat Ramana Rao; Shafer, Wilson D.; Jacobs, Gary; Davis, Burtron H.
Abstract : The effect of solvent on the hydrogen‐deuterium isotopic homomolecular exchange over a traditional Fischer‐Tropsch cobalt catalyst (25 % Co/Al2 O3 ) was investigated using a plug flow reactor at two different reaction temperatures (room temperature (26 °C) and –20 °C) and at atmospheric pressure. In this study, three different solvents were tested, including n‐ pentane, n‐ hexadecane, and C‐30 oil. The consumption of H2 and D2 is the same, and the concentration of the HD produced is twice the consumption of H2 or D2 at dry (without solvent) conditions. At room temperature and at –20 °C, conditions without solvent exhibited 100 mol% exchange with the formation of H2 :HD:D2 having a 1:2:1 ratio. For n‐ pentane solvent, the exchange rates were ∼97 and ∼80 mol% at 26 and −20 °C, respectively. For the n‐ hexadecane and C30 oil solvents, the initial exchange rate was ∼50 mol%, with the exchange rate decreasing over time. The lower exchange rate with the n‐ hexadecane and C30 oil solvents, and also n‐ pentane at –20 °C, is likely due primarily to the limited mobility of reactant molecules in the liquid‐filled pores of the catalyst. Blocking or covering of the pores of the catalyst depends on the molecular mass and density of the solvent. No isotopic partitioning preference was observed at two different temperatures and various solvents for the active cobalt catalyst.